Influence of light source and immersion media in surface roughness and hardness of a nanofilled composite resin - Santos, Patrícia Aleixo dos; Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Oliveira, Ana Luísa Botta Martins de [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Dibb, Regina Guenka Palma (My University, 2013)
The study evaluated the influence of light curing units and immersion media on superficial roughness and microhardness of the nanofilled composite resin Supreme XT (3M/ESPE). Light curing units used were: XL 3000 (3M/ESPE), Jet Lite 4000 Plus (JMorita) and Ultralume Led 5 (Ultradent) and immersion media were artificial saliva, Coke®, tea and coffee, totaling 12 experimental groups. Specimens (10mm x 2mm) were immersed in each respective solution for 5 seconds, three times a day, during 60 days and so, were submitted to measure of superficial roughness (Ra) and Vickers hardness. Data were subjected to two-way ANOVA test (p<0.05). Results showed that only the light source factor showed statistically difference for hardness. It was observed that the hardness of the composite resin Filtek Supreme XT (3M/ESPE) was influenced by the light source (p<0.01) independently of the immersion media (p= 0.35) and the Jet Lite 4000 Plus (JMorita) was the light curing unit that presented lower values. In relation to surface roughness, it was noted no-significant statistical difference for light source (p=0.84), when specimens were immersed in different beverages (p=0.35).
Keywords: Composite resin; Dental technology; Beverages